The fluorescent protein sensor roGFP2‐Orp1 monitors in vivo H2O2 and thiol redox integration and elucidates intracellular H2O2 dynamics during elicitor‐induced oxidative burst in Arabidopsis. Issue 3 (27th November 2018) - Nietzel, Thomas; Elsässer, Marlene; Ruberti, Cristina; Steinbeck, Janina; Ugalde, José Manuel; Fuchs, Philippe; Wagner, Stephan; Ostermann, Lara; Moseler, Anna; Lemke, Philipp; Fricker, Mark D.; Müller‐Schüssele, Stefanie J.; et al.
Summary: Hydrogen peroxide (H2 O2 ) is ubiquitous in cells and at the centre of developmental programmes and environmental responses. Its chemistry in cells makes H2 O2 notoriously hard to detect dynamically, specifically and at high resolution. Genetically encoded sensors overcome persistent shortcomings, but pH sensitivity, silencing of expression and a limited concept of sensor behaviour in vivo have hampered any meaningful H2 O2 sensing in living plants. We established H2 O2 monitoring in the cytosol and the mitochondria of Arabidopsis with the fusion protein roGFP2‐Orp1 using confocal microscopy and multiwell fluorimetry. We confirmed sensor oxidation by H2 O2, show insensitivity to physiological pH changes, and demonstrated that glutathione dominates sensor reduction in vivo . We showed the responsiveness of the sensor to exogenous H2 O2, pharmacologically‐induced H2 O2 release, and genetic interference with the antioxidant machinery in living Arabidopsis tissues. Monitoring intracellular H2 O2 dynamics in response to elicitor exposure reveals the late and prolonged impact of the oxidative burst in the cytosol that is modified in redox mutants. We provided a well defined toolkit for H2 O2 monitoring in planta and showed that intracellular H2 O2 measurements only carry meaning in the context of the endogenous thiol redox systems. This opens new possibilities to dissect plant H2 O2 dynamics and redox regulation, including intracellular NADPH oxidase‐mediated ROS signalling. Abstract : See also the Commentary on this article by McLachlan, 221 : 1180–1181 .